The Influence of Electronic Word of Mouth in Social Media on Generation Z’ Purchase Intentions: A Review - Ng, Alex, Hou Hong; Abdullah Saleem, Haroon; Lim, Kim Yew; Wong, Chee Hoo (INTI International University, 2019)
The advances of information technology and the emergence of online social media platforms have changed the way information is transmitted and have transcended the traditional limitations of WOM by bringing a new perspective for eWOM. Electronic word of mouth (eWOM) can reach a multitude of people at the same time and by that fact it shows its greater potential of becoming viral among a most global and multicultural generation – Z. Generation Z is born in the digital era. They are technologically native and the way they process information is different from other generations. Moreover, by 2019 Generation Z will account 31.5 percent of the whole world population. Therefore, it is crucial to understand the importance of Electronic Word of Mouth in Social Media on Generation Z' Purchase Intentions for any organization who is willing to succeed in the long run. This paper presents a preliminary review on the Influence of Electronic Word of Mouth in Social media on Generation Z purchase intentions. The purpose of this paper is to identify the research gap in the body of knowledge in context with electronic word of mouth (eWOM) influence in social media on Generation Z. Followed by developing research questions and research objectives.